1989
DOI: 10.1056/nejm198902093200604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High-Dose with Low-Dose Subcutaneous Heparin to Prevent Left Ventricular Mural Thrombosis in Patients with Acute Transmural Anterior Myocardial Infarction

Abstract: We performed a double-blind randomized trial comparing high doses of subcutaneous heparin (12,500 units every 12 hours) with low doses (5000 units every 12 hours) for 10 days in the prevention of left ventricular mural thrombosis in 221 patients with acute anterior myocardial infarction. Left ventricular mural thrombosis was observed by two-dimensional echocardiography on the 10th day after infarction in 10 of 95 patients (11 percent) in the high-dose group and in 28 of 88 patients (32 percent) in the low-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(89 citation statements)
references
References 15 publications
1
84
1
3
Order By: Relevance
“…Recent studies in adults with DVT have shown that achieving a therapeutic APTT early (within 48 h of initiating treatment) significantly reduces the rate of recurrence (30,(34)(35)(36)(37). Informal audits of heparin therapy in adult patients have shown that doseadjustment practices are often inadequate delaying the achievement of an APTT value above the minimum therapeutic level (20,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in adults with DVT have shown that achieving a therapeutic APTT early (within 48 h of initiating treatment) significantly reduces the rate of recurrence (30,(34)(35)(36)(37). Informal audits of heparin therapy in adult patients have shown that doseadjustment practices are often inadequate delaying the achievement of an APTT value above the minimum therapeutic level (20,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In order to combat this problem, samples from heparinized patients can be collected into an anticoagulant cocktail that inhibits platelet release, thereby avoiding PF4-mediated neutralization of heparin. It has been demonstrated that collection of blood into a citrate, theophylline, adenosine, dypyridamole mixture (CTAD) can greatly reduce the neutralization of heparin activity in blood (Contant et al, 1983;Van den Besselaar et al, 1987). In the study of Van den Besselaar et al (1987), APTTs of blood samples collected into CTAD were associated with less than 11% shortening depending on APTT reagent, compared with a 15±29% shortening of citrated APTTs between 1 h and 5 h after collection.…”
mentioning
confidence: 99%
“…The identification of high-risk patients and the pharmacological prevention of LVT formation are the key to preventing embolic events. Once an "at risk" patient is identified, treatment with heparin and then warfarin reduces the risk of LVT formation (43) and results in an 86% reduction in the rate of embolization (44). However effective, anticoagulation is not without risk.…”
Section: A Computational Methods That Simultaneously Resolves the Leftmentioning
confidence: 99%